Pengaruh Leverage, Pertumbuhan Perusahaan dan Kepemilikan Managerial terhadap Nilai Perusahaan dengan Enterprise Risk Management sebagai Pemoderasi - Sitorus, Frangky Yosua; Hulu, Indira Daryn; Sirait, Swanto (Media Akuntansi Perpajakan, 2025)
This research aims to examine the influence of leverage, company growth, and managerial ownership on company value. The company value in this study is measured using the Tobin's Q method. The data used in this research is secondary data sourced from the annual reports of energy sector companies listed on the Indonesia Stock Exchange (BEI), with Enterprise Risk Management (ERM) as a moderating variable for energy sector companies listed on the Indonesia Stock Exchange (BEI) during the period of 2022–2024. Data was obtained through purposive sampling of 35 energy sector companies with a total of 105 observations. The results of the study indicate that company growth has a positive and significant effect on company value, while leverage and managerial ownership do not have a significant effect. Enterprise Risk Management does not appear to strengthen the influence of leverage or managerial ownership on firm value, but weakens the influence of company growth on firm value. This research makes an important contribution to understanding the role of ERM as a moderator in the influence of financial variables and ownership on firm value, particularly in the dynamic and risky energy sector. These findings support trade-off, signaling, and agency theories, and highlight the importance of corporate risk management for the sustainability of firms in the energy sector